“A study of English-Vietnamese Translation of Journal-Article Abstracts” = Nghiên cứu việc dịch phần tóm tắt của một sốbài báo khoa học chuyên ngành từ tiếng Anh sang tiếng Việt - Nguyễn, Thị Huyền (ĐHNN, 2017)
This paper is intended to look at the theories of translation andthe theories of translation and the existing translation of scientific texts, and in a more detailed manner, of journal-article abstracts which belong to this text type. The knowledge, skills and experiences gained is then employed to deal with their English-Vietnamese translation of journal-article abstracts.